Case report: Rapid symptom relief in autoimmune encephalitis with efgartigimod: a three-patient case series - Zhang, Qianqian; Yang, Wenping; Qian, Yun; Zhang, Yu; Zhao, Huihui; Shu, Mingzhu; Li, Qingyang; Li, Yanan; Ding, Yu; Shi, Shiyu; Liu, Yaxi; Cheng, Xi; et al. (Frontiers in Immunology, 2024)
Introduction: Autoimmune encephalitis (AE) comprises a group of inflammatory brain disorders mediated by autoimmune responses. Anti–N-methyl-D-aspartate receptor (NMDAR) encephalitis, anti–leucine-rich glioma-inactivated 1 (LGI1) encephalitis, and anti–γ-aminobutyric acid-B receptor (GABABR) encephalitis are the most prevalent forms, characterized by the presence of antibodies against neuronal cell-surface antigens. Efgartigimod, an antagonist of the neonatal Fc receptor, has proven efficacy in myasthenia gravis treatment. This clinical case report describes the clinical progression and functional outcomes of AE in three patients who received efgartigimod treatment. Case presentations: Case 1 was a 60-year-old man exhibiting memory impairment and psychiatric disturbances over 11 days. Case 2 was a 38-year-old man with a 1-month history of rapid cognitive decline and seizures. Case 3 was a 68-year-old woman with mental behavioral changes and seizures for 4 months. Anti-GABABR, anti-LGI1, and anti-NMDAR antibodies were confirmed in the respective patients’ cerebrospinal fluid or serum. All three patients experienced marked and swift symptomatic relief after four cycles of efgartigimod treatment, with no complication. Conclusion: Current first-line and second-line treatments for AE have limitations, and efgartigimod has demonstrated potential in the rapid and efficacious treatment of AE, emerging as a promising option for the management of this disease.